2019
DOI: 10.1128/mcb.00248-19
|View full text |Cite
|
Sign up to set email alerts
|

Omomyc Reveals New Mechanisms To Inhibit the MYC Oncogene

Abstract: The MYC oncogene is upregulated in human cancers by translocation, amplification, and mutation of cellular pathways that regulate Myc. Myc/Max heterodimers bind to E box sequences in the promoter regions of genes and activate transcription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 50 publications
3
74
0
Order By: Relevance
“…By RNA-seq of colon carcinoma HCT116 cells treated with the Omomyc mini-protein, the authors confirmed the downregulation of Myc-driven gene signatures along with changes in the overall transcription profile. The downregulation of specific Myc targets such as ASNS, SAT1, ID3, and EGR2, as well as CD274-the gene encoding Programed death-ligand 1 (PD-L1)-was also verified by qPCR [82]. In the same study and in line with our own results, CoIP and proximity ligation assay showed that the Omomyc mini-protein forms homodimers and heterodimers with MYC and with MAX, and strongly reduces MYC/MAX dimers.…”
Section: The Omomyc Mini-protein Behaves As Its Transgenically-expressupporting
confidence: 81%
See 4 more Smart Citations
“…By RNA-seq of colon carcinoma HCT116 cells treated with the Omomyc mini-protein, the authors confirmed the downregulation of Myc-driven gene signatures along with changes in the overall transcription profile. The downregulation of specific Myc targets such as ASNS, SAT1, ID3, and EGR2, as well as CD274-the gene encoding Programed death-ligand 1 (PD-L1)-was also verified by qPCR [82]. In the same study and in line with our own results, CoIP and proximity ligation assay showed that the Omomyc mini-protein forms homodimers and heterodimers with MYC and with MAX, and strongly reduces MYC/MAX dimers.…”
Section: The Omomyc Mini-protein Behaves As Its Transgenically-expressupporting
confidence: 81%
“…In the same study and in line with our own results, CoIP and proximity ligation assay showed that the Omomyc mini-protein forms homodimers and heterodimers with MYC and with MAX, and strongly reduces MYC/MAX dimers. Omomyc/MYC dimers are present in the cytoplasm, while Omomyc/MAX and Omomyc/Omomyc are present also in the nucleus, reinforcing the notion that Omomyc sequesters Myc away from the DNA and binds E-boxes together with MAX or as a homodimer [82]. By E-box DNA binding pulldown coupled with mass spectrometry in lysates from Omomyc-treated Ramos cells, the same authors also confirmed that Omomyc effectively competes with MYC and MAX for DNA binding, but also with other PMN members MXI1, MGA, and MXD3, and with Myc cofactors WDR5 and KMT2A.…”
Section: The Omomyc Mini-protein Behaves As Its Transgenically-expresmentioning
confidence: 54%
See 3 more Smart Citations